Stigma association type and sponsor corporate image: Exploring the negative off-field behaviour of sportspeople. Issue 4 (November 2020) - Bloxsome, Ellen; Brown, Mark; Pope, Nigel; Joseph, Christopher
Highlights: Study of athlete negative off-field behaviour influence on sponsor corporate image. Behaviour effects not found to exist under simple association conditions. Behaviour affects sponsor corporate image under meaningful association conditions. Attribution judgments of associated entities are dependent on context of behaviour. Abstract: This paper examines how consumers' exposure to news-media reports of an athlete's negative off-field behaviour influences perceptions of a sporting team's sponsor. Stigma-by-association is proposed as an explanatory theory for the manner in which this process occurs. Two experiments were conducted on samples of both students and adults. Results indicate that off-field behaviour of athletes has no influence on consumer perceptions of sponsor corporate image under conditions of simple association. In contrast, significant changes in sponsor corporate image are found under meaningful association conditions. The results provide an understanding of how consumers make differential attribution judgments of associated entities dependent on the context of off-field behaviour. The research highlights implications for sponsors seeking to maximise the effectiveness of their sponsorship objectives. Chinese Abstract: 本文研究了新闻媒体报道的运动员场外消极行为的曝光会如何影响消费者对运动队赞助商的看法.联想标记被提出作为这一过程发生的方式的解释理论.研究人员以学生和成年人为样本进行了两个实验.结果表明, 在简单联想条件下, 运动员的场外行为对消费者对赞助商企业形象的认知没有影响.相比之下, 在有意义联想条件下, 赞助商的企业形象会发生显著变化.研究结果提供了消费者如何根据场外行为的情境对相关实体做出差异归因判断的理解.这项研究对于赞助想寻求其赞助目的的最大化有着显著的意义.